Atomistic Insights into the Stability of Pt Single-Atom Electrocatalysts - Speck, Florian; Paul, Michael T.Y.; Ruiz-Zepeda, Francisco; Gatalo, Matija; Kim, Haesol; Kwon, Han Chang; Mayrhofer, Karl; Choi, Minkee; Choi, Chang Hyuck; Hodnik, Nejc; Cherevko, Serhiy (Journal of the American Chemical Society, 2020)
Single-atom catalysts (SACs) have quickly emerged as a new class of catalytic materials. When confronted with classical carbon-supported nanoparticulated catalysts (Pt/C), SACs are often claimed to have superior electrocatalytic properties, e.g., stability. In this study, we critically assess this statement by investigating S-doped carbon-supported Pt SACs as a representative example of noble-metal-based SACs. We use a set of complementary techniques, which includes online inductively coupled plasma mass spectrometry (online ICP-MS), identical location transmission electron microscopy (IL-TEM), and X-ray photoelectron spectroscopy (XPS). It is shown by online ICP-MS that the dissolution behavior of as-synthesized Pt SACs is significantly different from that of metallic Pt/C. Moreover, Pt SACs are, indeed, confirmed to be more stable toward Pt dissolution. When cycled to potentials of up to 1.5 VRHE, however, the dissolution profiles of Pt SACs and Pt/C become similar. IL-TEM and XPS show that this transition is due to morphological and chemical changes caused by cycling. The latter, in turn, is a consequence of the relatively poor stability of S ligands. As monitored by online ICP-MS and XPS, significant amounts of sulfur leave the catalyst during oxidation. Hence, in case catalysts with improved stability in the anodic potential region are desired, more robust supports and ligands must be developed.
CRIS-Team Scopus Importer:2020-09-18